Externalities and Corporate Objectives in a World with Diversified Shareholder/Consumers - Hansen, Robert G.; Lott, John R. (Journal of Financial and Quantitative Analysis, 1996)
Robert G. Hansen, John R. Lott, Jr., Externalities and Corporate Objectives in a World with Diversified Shareholder/Consumers, The Journal of Financial and Quantitative Analysis, Vol. 31, No. 1 (Mar., 1996), pp. 43-68